Does country of resettlement influence the risk of labor market marginalization among refugees? A cohort study in Sweden and Norway - Ridwanul Amin; Ellenor Mittendorfer-Rutz; Karina Undem; Ingrid Sivesind Mehlum; Rachel Louise Hasting (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVES: This study aimed to compare the risk of labor market marginalization among refugees across different host countries of resettlement and examine the moderating role of birth country and length of stay on these associations. METHODS: Cohorts of refugees and native-born individuals aged 19-60 in Sweden (N=3 605 949, 3.5% refugees) and Norway (N=1 784 861, 1.7% refugees) were followed during 2010-2016. Rates (per 1000 person-years) of long-term unemployment, long-term sickness absence, and disability pension were estimated for refugees and the host populations. Cox regression models estimated crude and adjusted (for sex, age, educational level, and civil status) hazard ratio (HR_adj) for refugees compared to their respective host population, with 95% confidence intervals (CI). Analyses were also stratified by birth country and length of stay. RESULTS: Refugees in Norway and Sweden had a higher incidence of labor market marginalization compared to their host population. Refugees in Sweden had a comparatively lower relative risk of long-term unemployment but higher risk of disability pension (HR_adj 3.44, 95% CI, 3.38-3.50 and HR_adj 2.45, 2.35-2.56, respectively) than refugees in Norway (HR_adj 3.70, 3.58-3.82 and HR_adj 1.57, 1.49-1.66, respectively). These relative risks varied when stratifying by birth country. A shorter length of stay was associated with a higher risk of long-term unemployment and a lower risk of disability pension, with a stronger gradient in Sweden than in Norway. CONCLUSIONS: The relative risk of labor market marginalization varied by the refugees' birth country but followed similar trends in Sweden and Norway. Although speculative, these findings may hint at non-structural factors related to the refugee experience playing a more important role than host country structural factors for the risk of labor market marginalization among refugees. Future research, including host countries with more variability in structural factors, is required to further investigate these associations. The higher risk of long-term unemployment among refugees with shorter length of stay indicates a need for more efficient labor market integration policies for newly-arrived refugees.